2008
DOI: 10.1152/ajprenal.00214.2007
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the meprin metalloproteinase β gene protects against renal ischemia-reperfusion injury in mice

Abstract: Meprins are membrane-bound and secreted metalloproteinases consisting of alpha- and/or beta-subunits that are highly expressed in mouse kidney proximal tubules. Previous studies have implied that the meprin alpha/beta-isoform is deleterious when renal tissue is subjected to ischemia-reperfusion (I/R). To delineate the roles of the meprin isoforms in renal disease, we subjected mice deficient in meprin-beta (KO) and their wild-type (WT) counterparts to I/R. WT mice were markedly more susceptible to renal injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 49 publications
6
59
0
Order By: Relevance
“…Meprin subunits a and b cleave a variety of biologically active peptides; in particular, we want to point out gastrin and cholecystokin on one side (which are substrates for meprin b) and substance P and many cytokines on the other side (which are substrates for meprin a, see Sterchi et al, 2008). Meprins are expressed abundantly in epithelial cells of kidney, intestine and skin and recently a number of studies indicate their potential functions in pathological conditions, such as acute and chronic renal failures, diabetic nephropathy, colon carcinoma (Bylander et al, 2008;Lottaz et al, 1999;Red Eagle et al, 2005).…”
Section: M3 Familymentioning
confidence: 99%
“…Meprin subunits a and b cleave a variety of biologically active peptides; in particular, we want to point out gastrin and cholecystokin on one side (which are substrates for meprin b) and substance P and many cytokines on the other side (which are substrates for meprin a, see Sterchi et al, 2008). Meprins are expressed abundantly in epithelial cells of kidney, intestine and skin and recently a number of studies indicate their potential functions in pathological conditions, such as acute and chronic renal failures, diabetic nephropathy, colon carcinoma (Bylander et al, 2008;Lottaz et al, 1999;Red Eagle et al, 2005).…”
Section: M3 Familymentioning
confidence: 99%
“…These studies reported that several factors that exacerbate renal disease, such as kidney injury molecule-1, monocyte chemoattractant protein-1, meprin, and osteopontin, could serve as biomarkers for injury of the proximal tubule (PT) epithelium, progression of DN, renal ischemiareperfusion injury, and focal segmental glomerulosclerosis, respectively. [3][4][5][6] Typically, in order to discover new biomarkers, a comprehensive analysis of the genes that are upregulated in these diseases is essential. 7 Microarray is a very useful analytical method; however, a large number of the relevant genes might be affected by the genetic background of the patients and/or systemic diseases.…”
mentioning
confidence: 99%
“…Meprins hydrolyze a wide variety of peptides and proteins, such as growth factors, peptide hormones, and extracellular matrix proteins (11); however, their precise physiological role is not clear. The role of meprins has been studied in renal diseases, inflammation, and angiogenesis (4,10,20,27,38). It has been reported that meprin-␤ exacerbated the acute kidney injuries, whereas meprin-␣ was reported to be beneficial (10,20).…”
Section: Discussionmentioning
confidence: 99%
“…The role of meprins has been studied in renal diseases, inflammation, and angiogenesis (4,10,20,27,38). It has been reported that meprin-␤ exacerbated the acute kidney injuries, whereas meprin-␣ was reported to be beneficial (10,20). Meprin-␣ displayed proangiogenic properties in cell culture settings and in animal models (27,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation